“ …At lade hære marchere, heste trampe og kanoner buldre": Engels og Marx om den dansk-tyske krig i 1864 - Rasmussen, Palle (Arbejderhistorie - tidsskrift for historie, kultur og politik, 2012)
Palle Rasmussen: “…to set armies marching, horses stamping, and cannon thundering” Engels and Marx on the Danish-German War in 1864, Arbejderhistorie 1/2012, s. 66-83. Karl Marx and Frederick Engels attentively followed the economic and political developments of their time. This also included the conflicts between Denmark and Germany over the Schleswig-Holstein Question and the resultant war in 1864. Little was published by them on this issue but they did discuss the conflict in their private correspondence. Their assessments as to the causes and course of the conflict in 1864 mirrors some of the central themes in the Marxist social analysis, namely an understanding of the issues of national liberation and social revolution, national identity and ethnicity, and the great power context for social revolution. Marx and Engels did not reject the general relevance of national liberation movements but they did judge such movements pragmatically in relation to their role in the balance between reactionary and progressive forces. Concretely, they saw the movement for Schleswig-Holstein independence as doomed to fail. In his comments on the developments in Schleswig Engels sees national identity as a social construction which is marked by, amongst other things, the efforts of the bourgeois elite to create its own platform and the strategy of ruling powers to regulate daily life and culture. He does, though, also describe the characteristics of the population in racial terms or categories. In the context great power politics Marx and Engels ascribe to Russia the chief role as the strongest reactionary state in Europe. Marx, in particular, points to how the results experienced by Russia on other fronts determine the fact of its less robust intervention in the 1864 conflict. At the same time both Marx and Engels show how the Schleswig War plays a part in the advancement of Prussia as the dominant European power.